Student Thinking Interference with Various Types of Adversity Quotients while Solving Proportion Problems based on Information Processing Theory - Sari, Diah Prawitha; Suhendra; Al Jupri; Siti Fatimah; Isman M. Nur (Universitas Islam Negeri Raden Intan Lampung, 2026)
Adversity Quotient refers to a student’s capacity to respond to, manage, and overcome difficulties when facing challenges or problems. In this study, Adversity Quotient is examined in relation to information-processing theory, particularly in understanding how students experience thinking interference during problem solving. Through this theoretical perspective, the study investigates the causes of thinking interference encountered by students when solving direct and inverse proportion problems. Therefore, this study aims to analyze and describe the characteristics of thinking interference among students with different Adversity Quotient types in solving direct and inverse proportion problems based on information-processing theory. This study employed a qualitative approach with an exploratory descriptive design. The participants consisted of three students representing different Adversity Quotient types: one climber-type student (Subject S1), one camper-type student (Subject S2), and one quitter-type student (Subject S3). The findings revealed three categories of thinking interference: (1) direct thinking interference, (2) indirect thinking interference, and (3) mixed indirect thinking interference. It is expected that future researchers will further examine students’ thinking interference in relation to Adversity Quotient when solving direct and inverse proportion problems.